Cytokine Receptor Endocytosis: New Kinase Activity-Dependent and -Independent Roles of PI3K - Chen, Ping-hung; Yao, Huiyu; Huang, Lily Jun-shen (Frontiers in Endocrinology, 2017)
Type I and II cytokine receptors are cell-surface sensors that bind cytokines in the extracellular environment and initiate intracellular signaling to control processes such as hematopoiesis, immune function, cellular growth and development. One key mechanism that regulates signaling from cytokine receptors is through receptor endocytosis. In this mini-review, we describe recent advances in endocytic regulations of cytokine receptors, focusing on new paradigms by which PI3K controls receptor endocytosis through both kinase activity-dependent and -independent mechanisms. These advances underscore the notion that the p85 regulatory subunit of PI3K has functions beyond regulating PI3K kinase activity, and that PI3K plays both positive and negative roles in receptor signaling. On the one hand, the PI3K/Akt pathway controls various aspects downstream of cytokine receptors. On the other hand, it stimulates receptor endocytosis and down-regulation, thus contributing to signaling attenuation.